Respuesta :

Answer:

   Substitute the value of the variable into the expression and simplify.

                  --->  (38)

Answer:

38

Step-by-step explanation:

x² + 2y ÷ 2w + 3z if (w = 2) (x = 5) (y = 8) (z = 3)

Now switch the letters with the numbers that it was given

x² is (5²)

2y is (2 * 8)

2w is (2 * 2)

3z is (3 * 3)

Put these in the equation

5² + (2 * 8) ÷ (2 * 2) + (3 * 3)

Solve what is inside the parenthesis

5² + (16) ÷ (4) + (9)

get rid of the parenthesis

5² + 16 ÷ 4 + 9

Now solve it from here

5² "(5 * 5)" = 25

25 + 16 ÷ 4 + 9

you want to divide 4 into 16 first because of PEMDAS

25 + 4 + 9

29 + 9 = 38